AKIBAT HUKUM TERHADAP PELANGGARAN ATAS KETENTUAN HONORARIUM AKTA NOTARIS - Imam Suko Prayitno (Fakultas Hukum, Universitas Muhammadiyah Pontianak, 2019)
The increasing number of Notaries in Indonesia has resulted in violations of the honorarium provisions for Notary services that have been determined in the Notary Position Act (UUJN and Notary Ethics Code. The author in this study wants to examine and analyze further ratios regarding regulation of honorarium provisions Notary and legal consequences for Notaries for violating honorarium provisions in making deeds. The research method used is normative legal research, namely legal research conducted by examining library materials or secondary legal materials while the problem approach is carried out using a statute approach and conceptual approach The results of the study showed that the ratio of the regulation regarding the Notary honorarium as regulated in UUJN and the Notary Code of Ethics was to avoid unfair competition among Notaries. Violations committed by Notaries relating to honorariums. The arium making of the deed can result in a Notary being sanctioned based on the Notary Code of Ethics and based on UUJN in the form of verbal reprimand, written warning and temporary dismissal.